What I eat in a day videos: the influence of visual body cues on body dissatisfaction and eating intentions - Park, Sun Young; Bailey, Rachel L.; Park, Junho (Frontiers in Human Dynamics, 2025)
IntroductionThis study investigates how visual body cues in TikTok videos affect young viewers’ perceptions of body image and general eating intentions.MethodsIn this study, 78 female participants viewed six messages: three without body cues and three with either thin or muscular ideal cues in a randomized order in a 2 (thin ideal versus muscular ideal) × 3 (repetition of messages) × 2 (present vs. absence) mixed factorial design. After viewing each video, self-reported eating intentions and body dissatisfaction were measured.ResultsResults suggested that participants who view videos with body cues reported significantly lower eating intentions and higher body dissatisfaction. Although thin ideal cues led to higher body dissatisfaction compared to muscular ideal cues, no significant effect on eating intentions was found. Findings showed that body shape concerns significantly moderated the effects of body cues on body dissatisfaction and the effects of ideal cues on eating intentions, with individuals having higher body shape concerns experiencing more pronounced changes.DiscussionThese findings indicate that comparisons to influencers’ body ideals in TikTok “What I Eat in a Day” content can lower eating intentions and heighten body dissatisfaction, particularly among young women with body image concerns. Those results highlight the need for platform policies and body image interventions that separate food content from aesthetic ideals and instead promote functional, diverse body representations